Статуетки серезліївського типу як фактор контактів за доби пізнього енеоліту - Рассамакін, Ю.Я. (Археологія і давня історія України, 2021)
У зв’язку зі знахідкою нової статуетки серезліївського типу на поселенні майкопської культури «Чекон» в Прикубанні, дається порівняльний
аналіз цієї знахідки зі статуетками, відомими в
похованнях доби пізнього енеоліту у Дніпро-Бузькому межиріччі та Криму. Автор вважає знахідку з
Прикубання якісною імітацією, а посередниками
у появі такого типу антропоморфної пластики
далеко від основної зони її розповсюдження могло
бути мобільне населення, яке залишило на теренах
степового Причорномор’я поховання животилівсько-вовчанського типу. The author analyzes the find of a new clay figurine
of the Serezliіvka type at the Maikop culture settlement
«Chekon» in the Kuban region. This find can be
compared with figurines from burials of the Late Eneolithic
in the interfluve of the Dnieper and the Southern
Bug rivers. 25 figurines in 10 burials were found in this
region. One figurine is known from the Trypillia settlement
of Sandraki on the Southern Bug river (period
Trypillia C/II). Two figurines are known in the burial
on the Black Sea coast and one another in the Crimea.
Figurines of the Serzliivka type are typical for the
local Dnieper-Bug cultural group of the Late Eneolithic.
This local group is characterized by features of the
Lower Mikhailivka and Kvitiana cultures, as well as
elements of the Latest Trypillia. The character of the
clay of the statues is very close to the Tripolye ceramics
and is not typical for the steppe ceramic traditions.
The figurines have three form options in the design
of the head and specific ornamentation of the drawn
lines. The author notes the special features in the form,
ornament and technology of making a figurine from the
settlement «Chekon» in comparison with the Dnieper-
Bug region. This figurine is an imitation of «classic» figurines
from region between the Dnieper and Southern
Bug rivers. The mobile population, which left on the
territory of the Black Sea steppe burials of the Zhyvotylivka-
Vovchansk type, could be the mediators in the
emergence of this type of anthropomorphic sculpture
so far from the main zone of its distribution. In this
context, it is very important to note that ceramic products
were found in the settlement, analogies of which
are known in the settlements of Trypillia C/II. These
artefakts from the settlement are important for the development
of the concept of coexistence of the steppe
population of the Late Eneolithic in the context of the
development of agricultural societies.